Habilidades blandas y su influencia en el clima laboral de los servidores públicos del área administrativa y financiera del GADM Chone - Chavarría Cornejo, Karla Fernanda (2024)
The research was conducted with the purpose of analyzing the soft skills of public servants of the Municipal Decentralized Autonomous Government in Chone canton to determine their influence on the work environment. Three phases were developed corresponding to each of the specific objectives of the inquiry: first, the state of the art on the two study variables was established through an exhaustive bibliographic review of internal and external regulations on soft skills and the work environment. Then, a structured survey using the Likert scale was developed and applied to the public servants, and the results were analyzed. The second phase allowed for establishing the influence of soft skills on the work environment. Finally, in the third phase, an improvement plan was developed using the 5W+1H matrix to address identified weaknesses. The results demonstrated a significant relationship between the study variables, reaffirming the importance of possessing soft skills to improve the work environment. In conclusion, this research confirms the importance of strengthening these skills, making it essential to implement pertinent actions. Thus, a plan directed at the institution's authorities was proposed.